Glycan-dependent cell adhesion mechanism of Tc toxins - Daniel Roderer (Nature Portfolio, 2020)
Although Tc toxins are a major class of bacterial toxin translocation systems, little is known about their receptor binding. Here, the authors identify heparins/heparan sulfates and Lewis antigens as receptors for different Tc toxins, determine cryo-EM structures of three toxin-glycan complexes and propose a two-step cell adhesion mechanism for Tc toxins.